1989
DOI: 10.1002/jcp.1041410104
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of growth of human carcinoma SW‐13 cells by heparin and growth factors

Abstract: This study reports on the effects of heparin, basic and acidic fibroblast growth factors (bFGF and aFGF, respectively), and transforming growth factor type-e (TGFe) on the growth of a human adrenocortical carcinoma cell line, SW-13. Heparin has previously been shown to inhibit growth in several cell types, including smooth muscle cells, certain fibroblasts, and epithelial cells, and to modulate the effects of fibroblast growth factors. Whereas bFGF and aFGF bind tightly to heparin and elute from a heparin-Seph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Since we have shown that heparin does not inhibit the mitogenic effect of EGF, TGFa, or aFGF on keratinocytes or AKR-2B cells (data not shown), novel heparin-sensitive growth factors may have been produced by autonomously growing keratinocytes. In this regard, several other groups have reported potentially novel growth factors which display similar properties (Halper and Carter, 1989;Masuda et al, 1987). Heparin and heparan have been shown to exert antiproliferative effects on several cell types in vitro and in vivo (Hook et al, 1984;Shipley et al, 1989;Clowes and Karnovsky, 1977;Imamura and Mitsui, 1987;Majesky et al, 1987;Robertson and Goldstein, 1988;Wright et al, 1989).…”
Section: Heparin Sulfate Partially Blocks the Mitogenic Activity Of Kmentioning
confidence: 99%
“…Since we have shown that heparin does not inhibit the mitogenic effect of EGF, TGFa, or aFGF on keratinocytes or AKR-2B cells (data not shown), novel heparin-sensitive growth factors may have been produced by autonomously growing keratinocytes. In this regard, several other groups have reported potentially novel growth factors which display similar properties (Halper and Carter, 1989;Masuda et al, 1987). Heparin and heparan have been shown to exert antiproliferative effects on several cell types in vitro and in vivo (Hook et al, 1984;Shipley et al, 1989;Clowes and Karnovsky, 1977;Imamura and Mitsui, 1987;Majesky et al, 1987;Robertson and Goldstein, 1988;Wright et al, 1989).…”
Section: Heparin Sulfate Partially Blocks the Mitogenic Activity Of Kmentioning
confidence: 99%
“…Thus, these physiological components of the extracellular matrix have been defined "growth modulators" for two reasons: they bind growth factors -and possibly growth inhibitors -thus regulating their availability for receptor interaction at the cell surface; their effects could be either stimulatory or inhibitory on proliferation according to the cell type and/or to growth factor requirements (Gordon et al, 1987;Roberts et al, 1988). In fact, heparin stimulates endothelial cell growth (Sommer and Rifkin, 1989;Damon et al, 1989), whereas it inhibits the proliferation of vascular smooth muscle cells (Williams and Mason, 1991), renal mesangial cells (Adler and Eng, 1990), rat cervical epithelial cells (Striker et al, 1991), fibrib1asts (Striker et al, 1991), and transformed cell lines (Halper and Carter, 1989). Stimulation of endothelial cell growth by heparin is due to interaction with FGF (Fibroblast Growth Factor), leading to ligand/receptor stabilization (Sommer and Rifkin, 1989); however, the mechanism(s) underlying the growth inhibitory effects are 1065-6995/93/080781-06/$08.00 /0 still not completely defined.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its anticoagulant activity, HP has a variety of other biological and biochemical activities that include the following: 1) regulation of lipid metabolism (17), 2) control of blood fluidity at the endothelial surface (50), 3) control of cell attachment to various proteins in the extracellular matrix (ECM) (42,43,73), 4) binding with acidic and basic fibroblast growth factors (3,61), 5) binding to interleukin-3 and granulocyte-macrophage colony-stimulating factor (27,59), and 6) inhibition of serotonin-induced pulmonary artery (PA) smooth mus-cle cell (SMC) hypertrophy (44). HP stimulates endothelial cell growth (69), whereas it inhibits the proliferation of renal mesangial cells (65), rat cervical epithelial cells (1), transformed cell lines (5,16,30), and systemic SMCs and PASMCs (18,68). Of the types of biological activities just mentioned, anticoagulation has been extensively discussed in several reviews (6,15,36,48,76).…”
mentioning
confidence: 99%